LABORATORY ASSESSMENT OF VITAMIN D STATUS: METHODS AND DIAGNOSTIC CHALLENGES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Serum 25-hydroxyvitamin D [25(OH)D] is universally accepted as the best clinical indicator of an individual's vitamin D status and is the analyte measured for both diagnosis and monitoring of vitamin D deficiency. This preference is justified by the favourable kinetics of 25(OH)D, including its relatively long circulating half-life of approximately fifteen days, its stability in serum, its abundance relative to the active hormone, and its responsiveness to changes in both cutaneous synthesis and dietary intake. In contrast, the active hormone 1,25-dihydroxyvitamin D has a short half-life and is tightly regulated by parathyroid hormone, calcium, and phosphate, making it unsuitable as a marker of vitamin D reserves. Vitamin D deficiency is generally defined as a serum 25(OH)D concentration below 20 ng/mL (50 nmol/L), with insufficiency defined as 20-29 ng/mL (50-75 nmol/L) and sufficiency as 30 ng/mL (75 nmol/L) or above, although exact thresholds continue to vary between professional societies and have been subject to periodic revision.
Keywords: vitamin D, 25-hydroxyvitamin D, laboratory diagnosis, immunoassay, liquid chromatography-tandem mass spectrometry, assay standardisation, vitamin D deficiency